(untitled) (Cadernos de Sociomuseologia, 2026)
Recognized as a place of memory by former political prisoners, families of victims and disappeared political figures, human rights movements, parliamentarians and, more recently, by the state of Minas Gerais itself, the building of the former Department of Political and Social Order of Minas Gerais (DOPS/MG) was built in 1958 and became a symbol of institutionalized political repression during the Brazilian Military Dictatorship (1964-1985). The DOPS was dissolved in 1989, and after almost thirty years of social, institutional and political struggles, in 2017 the building was vacated as a police unit and designated for the implementation of the Human Rights Memorial (MDH), seeking to promote the re-signification of a place marked as a space of violation of fundamental rights. Through the analysis of the trajectory of the complex plot that culminated in the current MDH Project, we seek to reflect on the contribution that the museological approach can play in the implementation of an institution dedicated to dealing with traumatic memories and how in situ musealization can enhance a broader understanding of the materiality of a sensitive heritage. Keywords: Place of Memory; DOPS/MG; Traumatic Memory; In Situ Musealization; Human Rights Memorial of Minas Gerais.